Dmitriy Shostakovich in William Tanner Vollmann’s Novel “Europe Central” - Zinkevych, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
The relevance of the study. In the foreign reception of Dmitriy Shostakovich, its out-ofmusical-professional discourse is important. Along with the play by David Pounell “Master Class”, the novel by Julian Barnes “The Noise of Time” and others, the novel by the famous American writer William T. Vollmann (William T. Vollmann) “Europe Central” (“Europe nodal”) is quite significant, it received the 2005 US National Book Award. The almost 800-page epic, which foreign critics compare with the epic of L. Tolstoy and call “War and Peace of the 20th century”, covers the events of Russian and German history from 1914 till 1975, including the Holocaust, the era of great terror, Babi Yar. The panorama of the war between two totalitarian regimes is especially widespread. Among the characters are mainly representatives of creative professions and military leaders: Hitler and Stalin, Paulus and Vlasov, Kete Kolwitz and Anna Akhmatova, Tukhachevsky and Roman Carmen, etc. The destinies of all characters are intertwined, their stories unfold in parallel or in interaction. But the real hero of the book is Dmitriy Shostakovich. Main objective of the study is to acquaint with the work of William T. Vollmann and his novel “Europe Central”, the analysis of which makes it possible to understand the peculiarities of perception of D. Shostakovich’s music by the US intellectual elite. The main results and conclusions of the study. William T. Vollmann refers to Shostakovich as a hero and admits his passion for his personality. Mainly adhering to the facts, he conjectures a lot and frankly invents. Heightened metaphor, phantasmagorism, extravagance of his descriptions are quite consistent with the style of postmodernism or absurdity. The author does not hide his liberties and in the afterword apologizes for the distortions in the book. The mythogenic situation created by Vollmann clearly echoes the well-known — including Russian — fictionalization by Dmitriy Shostakovich. And, thus, Vollmann’s novel becomes another confirmation of Shostakovich’s acquisition of the status of a “cultural hero of the era”, because it is the mythogenic processes provoked by large-scale public reflection that are decisive in the formation of this sociocultural phenomenon.